Integrated management of processes and information - Shaw, Kenneth A. 1941- (2013 digital library., 2013)
Each step in a company's manufacturing, service, and information processes uses, creates, supplies, and stores information. In many businesses, the information processes are managed separately from other business processes. However, they should be considered together with other operations in a process to develop more effective and less-expensive methods for acquiring and using that information. Using a conversational tone, the author discusses a number of the procedural and managerial policy considerations for small and large businesses regarding information technology, process management, and business choices. The discussion focuses more on informing the reader about process-oriented concepts and management options available rather than providing specific recommendations regarding which process or information strategy to use.